IT project portfolio management - Bonham, Stephen S. (Artech House effective project management series., 2005)
This groundbreaking book introduces you to a comprehensive approach to implementing Project Portfolio Management (PPM) to support and prioritize IT projects in both large and small companies. The first book to show you how to manage the portfolio of all IT-based projects in an organization, this unique resource details how a portfolio of projects can be aligned with the ever-changing marketplace via a central strategy, maximized for overall return on investment, and balanced for risk across an organization. Written by a highly regarded industry professional with over 15 years of experience, th.